KEPADATAN DAN LAJU PERTUMBUHAN SPESIFIK Nannochloropsis sp. PADA KULTIVASI HETEROTROPIK MENGGUNAKAN MEDIA HIDROLISAT SINGKONG - Mujizat Kawaroe; Tri Prartono; Ganjar Saefurahman (Journal Omni-Akuatika, 2015)
Growth of Nannochloropsis sp. was observed in laboratory cultivation condition with enrichment of cassava hydrolysate into culture medium as follow : 25 ml microalgae strain, 75 ml seawater, without cassava hydrolysate (A); 25 ml microalgae strain, 25 ml cassava hydrolysate, 50 ml seawater (B), 25 ml microalgae strain, 50 ml cassava hydrolysate, 25 ml seawater (C). Cultivation condition was fixed as follow temperature 29°C, seawater pH 8, and salinity 30 ‰. Microalgae cultivation was performed at microalgae laboratory of Surfactant and Bioenergy Research Center using 100 ml Erlenmeyer covered by black plastic to prevent the influence of light. The specific growth rate of Nannochloropsis sp. was observed in 7 days for different cultivation medium composition. The highest density of microalgae was in the 4th days with 50ml cassava hydrolysate’s feeding (C treatment) about 172.661 cell/mL. The highest specific growth rate for Nannochloropsis sp. cultivation was observed in the 6th days without cassava hydrolysate’s feeding. Result of statistical analysis showed that different cassava hydrolysate’s feeding treatments (ml) in heterotrophically microalgae cultivation influenced the density of microalgae (cell/mL) but not influenced the specific growth rate of microalgae (per day).Keywords: Cassava hydrolysate, Density, Heterotrophic cultivation, Spesific growth rate, Nannochloropsis sp.